PENGARUH UKURAN PERUSAHAAN, STRUKTUR AKTIVA, PROFITABILITAS, GROWTH, DAN LIKUIDITAS TERHADAP STRUKTUR MODAL (Studi empiris Pada Perusahaan Manufaktur Yang Terdaftar Di BEI Periode 2012-2016) - Gigih Puja Priyagung (Universitas Sarjanawiyata Tamansiswa, 2019)
This research is conducted for the very purpose of knowingthe influence of business risk, assets structure, profitability andfirm size on capital structure. Manufacture companies listed onIndonesian stock exchange for the period of 2010-2014 are chosento be the objects of the research. Using purposive samplingmethod, the number of objects to 44 companies from a total of124 observed companies. The data are analyzed with multiplelinear regression.The result of the Research it self are as such; firm size givesnegative influence and is significant on capital structure, assetsstructure gives positive influence and is significant on capitalstructure, profitability gives negative influence and is significanton capital structure, growth gives positive influence and issignificant on capital structure, and liquidity gives negativeinfluence and is significant on capital structure.Key words : firm size (SIZE), assets structure (TA) , profitability (ROI), GROWTH(GROWTH), liquidity (CR) and capital structure (DER)